Fasting blood glucose to HDL-C ratio as a novel predictor of clinical outcomes in non-diabetic patients after PCI. Issue 12 (23rd December 2020) - Guo, Qian-Qian; Zheng, Ying-Ying; Tang, Jun-Nan; Wu, Ting-Ting; Yang, Xu-Ming; Zhang, Zeng-Lei; Zhang, Jian-Chao; Yang, Yi; Hou, Xian-Geng; Cheng, Meng-Die; Song, Feng-Hua; Liu, Zhi-Yu; et al.
Abstract: Background The present study was to assess the prognostic value of fasting blood glucose to high-density lipoprotein cholesterol ratio (GHR) in non-diabetic patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). Methods and results A total of 6645 non-diabetic patients from two independent cohorts, the CORFCHD-PCI study ( n =4282) and the CORFCHD-ZZ ( n =2363) study, were enrolled in Clinical Outcomes and Risk Factors of Patients with Coronary Heart Disease after PCI. Patients were divided into two groups according to the GHR value. The primary outcome included all-cause mortality (ACM) and cardiac mortality (CM). The average follow-up time was 36.51 ± 22.50 months. We found that there were significant differences between the two groups in the incidences of ACM ( P =0.013) and CM ( P =0.038). Multivariate Cox regression analysis revealed GHR as an independent prognostic factor for ACM. The incidence of ACM increased 1.284-times in patients in the higher GHR group (hazard ratio [HR]: 1.284 [95% confidence interval [CI]: 1.010–1.631], P <0.05). Kaplan–Meier survival analysis suggested that patients with high GHR value tended to have an increased accumulated risk of ACM. However, we did not find significant differences in the incidence of major adverse cardiac events, main/major adverse cardiovascular and cerebrovascular events (MACCE), stroke, recurrent myocardial infarction (MI) and bleeding events. Conclusions The present study indicates that GHR index is an independent and novel predictor of ACM in non-diabetic CAD patients who underwent PCI.